German bronchoscopy unit readiness for the COVID-19 pandemic: a nationwide survey. Issue 3 (31st August 2020) - Heidemann, Clara S.; Garbe, Jakob; Damm, Marko; Walter, Steffen; Michl, Patrick; Rosendahl, Jonas; Darwiche, Kaid; Eisenmann, Stephan
Background: The worldwide impact of the coronavirus disease 2019 (COVID-19) pandemic is unprecedented. Among the aerosol generating procedures, bronchoscopy in particular is an indispensable diagnostic and therapeutic tool that comes with a high risk of infection. Therefore, national societies have issued guidance statements. However, the individual ability of bronchoscopy units to follow these recommendations is largely unknown. Methods: We conducted a nationwide survey from 1 April 2020 to 7 April 2020 to which 218 German endoscopy units, 105 solely bronchoscopy and 113 interdisciplinary, responded. The survey was distributed electronically via the German Respiratory Society. Results: While 17% of units did not cancel any interventions, 16% cancelled >80% of their interventions. 73% were unable to completely separate high-risk patients. Most procedural measures, such as risk stratification in patients (95%), training to handle COVID-19 patients and personal protective equipment (PPE) (91%), risk adapted use of PPE (85%) and self-monitoring for staff (84%) were adopted well. Unit managers expected shortages in PPE (74%), staff shortages (68%) and severe financial losses (63%). Conclusion: In the short-term, PPE shortages are perceived to be the most imminent threat to bronchoscopic activity as a whole. In this era of uncertainty, sound evidence to guide bronchoscopy units and an international concerted effort are urgently needed to formulate recommendations on facts and adapted to local conditions as described in this study. Bronchoscopy units were partly prepared for the #COVID19 pandemic. However, sound evidence to guide units and an international concerted effort are urgently needed to formulate recommendations for future pandemics. https://bit.ly/2B8WOPe